Utilization of Visual Communication ‘Nice Photos’ as Political Communication Media in Increasing Public Participation (Case Study of West Java DPD Candidate Komeng) - Rizkia, Nanda Dwi; Euis Komalawati (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Political communication, especially at the campaign level of candidates for the Regional Representative Council (DPD) like Komeng in West Java, utilizes visual media strategies such as ballot papers as significant campaign tools. This research adopts a quantitative approach with primary data gathered through interviews and documentation from key informants, including members of the KPU (General Election Commission), Bawaslu (Election Supervisory Agency), TKN (Campaign Team), and the general public. Simple random sampling method was employed to collect data, which was then analyzed using straightforward data processing techniques. The research findings indicate that the Political Communication conducted by Komeng has been able to create a political entertainment stage amidst intense political competition. This concept of political entertainment, highlighting cheerfulness amidst political tension, has resonated strongly with voters emotionally. This strategy successfully garnered public sympathy and increased Komeng's presence in the political arena. Visual communication leveraging Komeng's humorous character provided a positive affective stimulus to voters, thereby fostering positive interactions